Berberine alleviates enterotoxigenic Escherichia coli-induced intestinal mucosal barrier function damage in a piglet model by modulation of the intestinal microbiome - Du, Min; Liu, Xinran; Ji, Xu; Wang, Yue; Liu, Xiaodan; Zhao, Chunfang; Jin, Erhui; Gu, Youfang; Wang, Hongyu; Zhang, Feng (Frontiers in Nutrition, 2025)
IntroductionEnterotoxic Escherichia coli (ETEC) is the main pathogen that causes diarrhea, especially in young children. This disease can lead to substantial morbidity and mortality and is a major global health concern. Managing ETEC infections is challenging owing to the increasing prevalence of antibiotic resistance. Berberine, categorized as a substance with similarities in “medicine and food,” has been used in China for hundreds of years to treat gastrointestinal disorders and bacteria-induced diarrhea. This study investigated the preventive effect of dietary berberine on the intestinal mucosal barrier induced by ETEC and the microbial community within the intestines of weaned piglets.MethodsTwenty-four piglets were randomly divided into four groups. Piglets were administered either a standard diet or a standard diet supplemented with berberine at concentrations of 0.05 and 0.1%. and orally administered ETEC or saline.ResultsDietary supplementation with berberine reduced diamine oxidase, d-lactate, and endotoxin levels in piglets infected with ETEC (P < 0.05). Berberine increased jejunal villus height, villus/crypt ratio, mucosal thickness (P < 0.05), and goblet cell numbers in the villi and crypts (P < 0.05). Furthermore, berberine increased the optical density of mucin 2 and the mucin 2, P-glycoprotein, and CYP3A4 mRNA expression levels (P < 0.05). Berberine increased the expressions of zonula occludins-1 (ZO-1), zonula occludins-2 (ZO-2), Claudin-1, Occludin, and E-cadherin in the ileum (P < 0.05). Moreover, berberine increased the expression of BCL2, reduced intestinal epithelial cell apoptosis (P < 0.05) and decreased the expression of BAX and BAK in the duodenum and jejunum, as well as that of CASP3 and CASP9 in the duodenum and ileum (P < 0.05). Berberine decreased the expression of IL-1β, IL-6, IL-8, TNF-α, and IFN-γ (P < 0.05) and elevated total volatile fatty acids, acetic acid, propionic acid, valeric acid, and isovaleric acid concentrations (P < 0.05). Notably, berberine enhanced the abundance of beneficial bacteria including Enterococcus, Holdemanella, Weissella, Pediococcus, Muribaculum, Colidextribacter, Agathobacter, Roseburia, Clostridium, Fusicatenibacter, and Bifidobacterium. Simultaneously, the relative abundance of harmful and pathogenic bacteria, such as Prevotella, Paraprevotella, Corynebacterium, Catenisphaera, Streptococcus, Enterobacter, and Collinsella, decreased (P < 0.05).DiscussionBerberine alleviated ETEC-induced intestinal mucosal barrier damage in weaned piglets models. This is associated with enhancement of the physical, chemical, and immune barrier functions of piglets by enhancing intestinal microbiota homeostasis.